2019
DOI: 10.30924/mjcmi.24.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate social disclosure practice on reporting quality

Abstract: This research is striving to provide an insight into the importance of Corporate Social Responsibility (CSR) for the insurance sector while aiming to examine various corporate social responsibility initiatives undertaken by insurance companies in Croatia. There is a broad range of potential benefits from CSR for insurance companies such as long-term sustainability and profitability, yet only several research studies on CSR practices have thus far been conducted on the insurance sector. Hence, the purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Most of the CSRD studies conducted in the financial sector used annual reports and sustainability reports as sources to determine the levels of CSR information (for example, Khan, 2010; Menassa, 2010; Kilic and Kuzey, 2019). The focus on both the annual and sustainability reports may be due to the consideration of both reports by the investors, customers, business partners and other stakeholders as highly credible sources of information (El-Bassiouny et al , 2018; Dropulic and Cular, 2019). Moreover, past studies exploring on the communication medium for CSR practices amongst the firms in financial sector revealed that the financial institutions prefer to communicate their CSR practices in annual reports or sustainability reports rather than in their websites (for example, Sobhani et al , 2012 (Bangladesh); Matuszak and Rozanska, 2017 (Poland); Dropulic and Cular, 2019 (Croatia)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the CSRD studies conducted in the financial sector used annual reports and sustainability reports as sources to determine the levels of CSR information (for example, Khan, 2010; Menassa, 2010; Kilic and Kuzey, 2019). The focus on both the annual and sustainability reports may be due to the consideration of both reports by the investors, customers, business partners and other stakeholders as highly credible sources of information (El-Bassiouny et al , 2018; Dropulic and Cular, 2019). Moreover, past studies exploring on the communication medium for CSR practices amongst the firms in financial sector revealed that the financial institutions prefer to communicate their CSR practices in annual reports or sustainability reports rather than in their websites (for example, Sobhani et al , 2012 (Bangladesh); Matuszak and Rozanska, 2017 (Poland); Dropulic and Cular, 2019 (Croatia)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As various authors state [31][32][33][34], CSR and sustainability [5,35] have acquired increasing importance as strategic factors for the survival and the achievement of long-lasting competitiveness in the market [36][37][38][39][40]. Company performance can no longer be assessed only on the basis of the economic dimension, but also on the social and environmental dimension [41].…”
Section: The Linkage Between Sustainability Reporting and The Sustainmentioning
confidence: 99%
“…According to Kavitha and Anuradha (2016), social responsibility "is the commitment of companies to provide resources that work towards social development." Dropulić and Cular (2019) have defined social responsibility as the relationship between the organization and society.…”
Section: Social Responsibilitymentioning
confidence: 99%
“…They found that government and customer pressure led to a positive correlation with banks' social disclosure. Dropulić and Cular (2019) examined various corporate social responsibility initiatives undertaken by insurance companies in Croatia and their effect on reporting quality. They found that insurance and reinsurance companies in Croatia do not have a high level of corporate social responsibility online disclosure Garcia et al (2018) investigated the influence of social disclosure on the relationship between Corporate Financial Performance and Corporate Social Performance.…”
Section: Introductionmentioning
confidence: 99%